Earnings Quality of Companies Listed on The Indonesian Stock Exchange - Ni Putu Erviani Astari; Made Yessi Puspitha; Ni Komang Urip Krisna Dewi; Ni Kadek Erina Purnamasari Dewi (Jurnal Ekonomi dan Bisnis Jagaditha, 2023)
Earnings is one of the indicators used in assessing company performance and investment decisions making process. Entities that have high profit does not necessarily have high-quality earnings. This study analyzes the earnings quality of companies listed on the Indonesia Stock Exchange from 2017 to 2021. The sample in this study was 272 companies which were determined using the purposive sampling method. This study uses secondary data, namely financial statements and closing stock price information consisting of 3 days before, the day of publication of financial statements, and 3-days after publication. The study sample analyzed with the Earnings Response Coefficient (ERC). Tests are carried out every year from 2017 to 2021 using the regression test. The test results show that there is no increase in the quality of earnings for companies listed on the Indonesia Stock Exchange. The test results also show that earnings quality decreased from 2017 to 2021. Thus, stakeholders can use other financial indicators or combine profit indicators with different hands in the investment decisions making process and in evaluating company performance.